The Cham Muslims in Ninh Thuan Province, Vietnam - Nakamura, Rie (Center for Integrated Area Studies, Kyoto University, 2008)
This paper discusses the Cham communities in Ninh Thuan Province, Vietnam. The Cham people are one of 54 state recognized ethnic groups living in Vietnam. Their current population is approximately 130,000. They speak a language which belongs to the Malayo-Polynesian language family. In the past, they had a country called, Champa, along the central coast of Vietnam, which was once prosperous through its involvement in maritime trade. While the largest concentration of the Cham people in Vietnam is found in a part of the former territory of Champa, particularly Ninh Thuan and Binh Thuan provinces, there is another group of Cham people living in the Mekong Delta, mostly in An Giang province near the border with Cambodia. There are differences in ethnic self-identification between these two groups of Chams living in the different localities. In general, the Chams living in the former territory of Champa equate being Cham as being descendants of Champa while the Chams of the Mekong Delta view being Cham as being Muslim. This paper is an attempt to understand the ethnicity of the Cham communities in Ninh Thuan Province through their religious system, particularly a dual structural principle in Cham cosmology called Awar and Ahier. In this paper, I argue that the concepts of Ahier and Awar, hold the key to understanding the way their ethnicity has been constructed and reveals an interesting aspect of their world view. In the course of the discussion, their indigenized form of Islam called Bani religion, which is peculiar to the Cham community will be introduced.